Cervical spine trauma - Vialle, Luiz Roberto; Oner, F. Cumhur; Vaccaro, Alexander R. (AOSpine masters series, 2015)
This fifth volume in the AOSpine Masters Series presents a detailed analysis of the essential aspects of managing the most common cervical spine injuries. World-renowned cervical spine experts discuss anatomy, biomechanics, patient evaluation, and critical steps in the decision-making process for the treatment of these complex injuries. Chapters include: Anatomy of the Cervical Spine, Nonoperative Management of Cervical Spine Trauma, and Subaxial Cervical Spine Injuries